2017
DOI: 10.1039/c7mb00280g
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA SNHG17 is an unfavourable prognostic factor and promotes cell proliferation by epigenetically silencing P57 in colorectal cancer

Abstract: Recently, substantial evidence has demonstrated that long non-coding RNAs (lncRNAs) play critical roles in multiple cancers including colorectal cancer (CRC). Utilizing publicly available lncRNA-expression-profiling data from the Gene Expression Omnibus (GEO) dataset GSE21510, we screened SNHG17 as a new candidate lncRNA associated with CRC development and progression. We further demonstrated that SNHG17 was upregulated in CRC tissues, and that its overexpression was significantly correlated with tumor size, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 35 publications
7
73
0
Order By: Relevance
“…A large number of published works have reported that these lncRNAs play an important role in multiple tumors . Our previous research shows that lncRNA SNHG17 can promote the proliferation of CRC cells by inhibiting the expression of p57 . The high expression of lncRNA LL22NC03‐N64E9.1 could predict poor prognosis in patients with colon cancer .…”
Section: Discussionmentioning
confidence: 97%
“…A large number of published works have reported that these lncRNAs play an important role in multiple tumors . Our previous research shows that lncRNA SNHG17 can promote the proliferation of CRC cells by inhibiting the expression of p57 . The high expression of lncRNA LL22NC03‐N64E9.1 could predict poor prognosis in patients with colon cancer .…”
Section: Discussionmentioning
confidence: 97%
“…There are also many types of lncRNAs that have been studied. Growing evidence suggests that lncRNAs are closely related with tumor . For example, lncRNA H19 promotes breast cancer progression, and plasma circulating lncRNA H19 can also serve as a screening and diagnostic marker for early breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies investigated the expression patterns of P57 in CRC tissues, and highlighted P57 as an important anti-oncogene in CRC progression [47, 48]. We also reported that lncRNA HOXA-AS2 mediated CRC proliferation partly through inhibiting P21 and KLF2 expression [30].…”
Section: Resultsmentioning
confidence: 99%
“…P57 is a crucial component of CKIs family, which also includes P15, P16, P21, and P27 [47]. Our previous studies investigated the expression patterns of P57 in CRC tissues, and highlighted P57 as an important anti-oncogene in CRC progression [47, 48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation